The Relationship between Work Engagement and Eudaimonic Workplace Well-Being among Nurses at RSUD Pasaman Barat - Vinnatha Syella. JD; Suci Rahma Nio (Darul Yasin Al Sys, 2026)
Work engagement and eudaimonic workplace well-being are increasingly important in the health-care sector, where nurses are required to deliver continuous, professional, and emotionally demanding services. Although previous studies have widely examined work engagement, burnout, job satisfaction, and general workplace well-being among nurses, research specifically addressing the relationship between work engagement and eudaimonic workplace well-being in regional public hospitals in Indonesia remains limited. This study aims to analyze the relationship between work engagement and eudaimonic workplace well-being among nurses at RSUD Pasaman Barat. A quantitative correlational design was employed, involving 172 nurses selected through purposive sampling. Data were collected using the Eudaimonic Workplace Well-Being Scale and the Utrecht Work Engagement Scale-9 and were analyzed using Pearson Product Moment correlation and simple regression with IBM SPSS for Windows. The findings indicate a positive and significant relationship between work engagement and eudaimonic workplace well-being, with a correlation coefficient of 0.487 and a significance value of 0.000. Regression analysis further showed that work engagement contributed 23.7% to eudaimonic workplace well-being. These findings contribute to the theoretical development of work engagement and eudaimonic workplace well-being within organizational psychology and nursing management. The study concludes that work engagement plays an important role in strengthening nurses’ meaningful psychological well-being at work. Practically, hospital management is encouraged to create a supportive work environment through stronger social support, professional development, recognition, and healthy workload management.